Quality of Life Assessment after Pancreatic Enzyme Replacement Therapy in Chronic Pancreatitis. (1st October 2003) - Czakó, László; Takács, Tamás; Hegyi, Peter; Prónai, László; Tulassay, Zsolt; Lakner, Lilla; Döbrönte, Zoltán; Boda, Krisztina; Lonovics, János
Abstract : GOALS: To evaluate the quality of life (QoL) of patients with chronic pancreatitis before and after pancreatic enzyme replacement therapy in a prospective, multicentre, follow-up study. STUDY: Two groups of patients were evaluated. Group 1 consisted of 31 patients with newly diagnosed chronic pancreatitis who had never been treated with pancreatic enzyme preparations. Group 2 consisted of 39 patients whose disease was diagnosed on average 3.4 years before the start of the study. The latter group of patients had undergone pancreatic enzyme replacement therapy, but during follow-up this treatment proved to be insufficient. The dose of pancreatic enzyme replacement therapy was tailored in accordance with the degree of pancreatic exocrine insufficiency measured by means of exocrine pancreatic function tests. A modified European Organizaton for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 (EORTC QLQ-C30) was used to assess QoL. RESULTS: The social functioning and financial strain were significantly better, while the levels of hope and confidence were significantly reduced in group 1 compared with group 2. A significant gain in body weight and a significantly reduced defecation rate were found in both groups one month after the beginning of the pancreatic enzyme replacement therapy when compared with the pretreatment values. The prevalence of general and disease-specific symptoms and the intensity of pain were reduced in both groups after one month of enzyme substitution therapy. The working ability, the financial strain and the overall QoL scores were improved significantly in both groups, while the cognitive functioning score was found to be significantly improved during the follow-up only in group 1. The overall increase in the QoL score correlated significantly with the increase in body weight and the decrease in defecation number in both groups. CONCLUSIONS: Pancreatic enzyme replacement therapy in patients with chronic pancreatitis not only reduced the extent of steatorrhea and pain, but also significantly improved a variety of other symptoms and the patient's QoL. Individually tailored enzyme replacement therapy improved the QoL not only in the untreated chronic pancreatitis patients, but also in the inadequately treated group. This study demonstrated that the EORTC QLQ-C30 questionnaire, with the addition of two further questions about steatorrhea, is a useful tool for the evaluation of QoL in patients with chronic pancreatitis.